THE MODERN STATE OF CREDIT OPERATIONS IN FINANCIAL SERVICE INSTITUTIONS OF OUR COUNTRY - Fayziyev Hamid Abdijabborovich (Western European Studies, 2025)
This article examines the contemporary condition of credit operations within the financial service institutions of Uzbekistan.It explores the structural evolution of the national credit system and the factors shaping its current functionality. Particular attention is given to regulatory reforms that have strengthened institutional transparency and risk management. The study analyzes how digitalization has transformed lending procedures and improved service accessibility. It evaluates the role of commercial banks, microfinance organizations, and non-bank institutions in expanding credit supply.The paper highlights challenges related to credit risk, collateral requirements, and borrower assessment.It reviews the influence of monetary policy on lending dynamics and financial stability. Empirical observations illustrate the growing diversification of credit products in various economic sectors.The research underscores the importance of financial literacy for sustainable credit development.The article identifies strategic priorities for enhancing credit efficiency and institutional capacity. It also assesses the socioeconomic impact of modern credit practices on entrepreneurship and households.Overall, the study provides a comprehensive and evidence-based overview of credit operations in Uzbekistan’s financial services sector.
Keywords: Credit operations; financial institutions; lending reforms